When amputation is not the end of the challenge: A successful therapy for osteomyelitis and soft tissue infection in a patient with type 1 diabetes - Paola Caruso; Maurizio Gicchino; Miriam Longo; Lorenzo Scappaticcio; Ferdinando Campitiello; Katherine Esposito (Journal of Diabetes Investigation, 2022)
Abstract Infection is a common complication in patients with diabetic foot ulcer, leading to lower extremities amputation and healing failure. In this article, we report the case of a 39‐year‐old man with diabetes who developed a severe soft tissue infection and osteomyelitis after experiencing a major amputation for wet gangrene of both the foot and the ankle.